2022
DOI: 10.1186/s12870-022-04007-8
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of mechanism of high quality and yield of Gastrodia elata Bl. f. glauca by the isolation, identification and evaluation of Armillaria

Abstract: Background Gastrodia elata Bl. f. glauca, a perennial herb of G.elata Bl. in Orchidaceae, is one of the most valuable traditional Chinese medicines. G. elata Bl. is a chlorophyll-free myco-heterotrophic plant, which must rely on the symbiotic growth of Armillaria, but not all Armillaria strains can play the symbiotic role. Additionally, Armillaria is easy to degenerate after multiple generations, and the compatibility between the strains from other areas and G. elata Bl. f. glauca in Changbai M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 82 publications
1
14
0
Order By: Relevance
“…A previous study conducted with five Armillaria isolates reported a positive effect of an excellent Armillaria strain on the promotion of quality and yield of G. elata Bl. f. glauca in Changbai Mountain ( Yu et al, 2022 ). The researchers found that excellent Armillaria strains increased the yield of G. elata Bl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study conducted with five Armillaria isolates reported a positive effect of an excellent Armillaria strain on the promotion of quality and yield of G. elata Bl. f. glauca in Changbai Mountain ( Yu et al, 2022 ). The researchers found that excellent Armillaria strains increased the yield of G. elata Bl.…”
Section: Discussionmentioning
confidence: 99%
“…Being one of the heterotrophic plants without chlorophyll, the growth and development of G. elata require symbiosis with Armillaria for nutrient supply since the protocorm stage ( Yuan et al, 2018 ). The Armillaria members impose a significant impact on the yield and quality of G. elata ; therefore, the isolation and identification of excellent Armillaria strains are of great significance ( Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The seeds of G. elata do not contain an endosperm, so their germination and development into protocorms only occur when they are provided with adequate nutrients through the digestion of fungal strains of Mycena spp. The juvenile tubers of G. elata subsequently grow through a symbiotic association with a mycorrhizal fungus Armillaria mellea to yield mature tubers ( Park and Lee, 2013 ; Chen et al, 2019 ; Yu et al, 2022 , 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“… Zheng et al (2023) compared the diversity and structure of endophytic bacterial communities in G. elata tubers grown in various geographical regions. The effects of different Armillaria strains ( Yu et al, 2022 ; Wang et al, 2023 ) and Mycena strains ( Yu et al, 2023 ) on the structure and metabolic function of soil microbial communities, as well as the quality and productivity of G. elata have also received recent research attention.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, GR has the highest annual production, and GB has the highest price on market. That is mainly because GB was not only good in quality but also sweet in taste ( Yu E. et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%